SEROLOGIC PREVALENCE OF TOXOPLASMOSIS IN SHEEP, GOATS CATTLE. AND PIGS FROM YOGYAKARTA - Sri Hartati (Jurnal Sain Veteriner, 1999)
The purpose of the investigation is to find out the serologically prevalence oT toxoplasrnosis in animal husbandry primarily in sheep, goats, cattle and pigs-Serum samples were taken from 100 sheep. 50 goats, 50 cattle and 100 pigs in a Yogyakarta abattoir. The sera were examined for Toxoplasma gonddi antibody by using direct agglutination test with Toxo-Scrven DA. It was considered that titers of 1:40 or greater were positive.The obtained results showed that prevalence of antibodies to T. gondii were : Sheep 50%, goats 15&. cattle 2% and pigs 44X. The sex was no err 1.1 on the prevalence of toxoplasmosis.